This is life : (Holt, Rinehart and Winston, 1962)
Contents: Photosynthesis; energy release and utilization; ultrastructure of cells in relation to function; nutrition of protists; viruses: Reproduction and heredity; Bacteria: Reproduction and heredity; Structure of the genetic material and the concept of the gene; plant growth and plant hormones; plant morphogenesis; animal morphogenesis; the role of hybridization in evolution; the origin of life.